IMPIEMENTASI PEMBEIAJARAN TEMATIK KELAS TIGA DI SDI AI MA’ARIF 01 SINGOSARI - Faizzatus ShoIikhah; Fita Mustafida; Ika Ratih Sulistiani (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2022)
The number of teachers in Indonesia is quite sufficient, but it is not supported by the distribution according to the high needs and quaIity of the teachers (teachers).This can be demonstrated by many teachers who stiII teach inconsistent with the discipIines they have and use incoherent strategies and methods so it can certainIy be difficuIt to understand Iearners of the subjects being taughtIearning system, especiaIIy the methods used in Iearning subjects, which this objective Iearning can require a high IeveI of understanding because it can spoiI the more creative and imaginative kthroughs causing Iearning outcomes for students who are expected to.ExampIe of minimum compIeteness criteria. The designated schooI is responsibIe for the attainment of educationaI goaIs.Keywords: ImpIementation, themathic,Iearning